Single Layer Wide Angle Microwave Absorber for X band Application with Bandwidth Enhancement - Herman Koto, Muhammad Ikmal Harris; Elfarizanis Baharudin, (Evolution in Electrical and Electronic Engineering, 2022)
Designing wide bandwidth absorption with smaller thickness has become a challenge when designing microwave absorbers. Therefore, in this paper, a single-layer wide-angle microwave absorber for X-band application with bandwidth enhancement is presented. The microwave absorber is made up of three layers, a top layer with a double-ring resonator, a substrate layer of FR4 and a ground copper layer. In this study, the design and the analysis have been done using CST Microwave Studio on the substrate design and the parameter of the ring resonator. From the result, the designed microwave absorber is able to absorb more than 90% absorption rate from 8.344 GHz to 12.304 GHz. The microwave absorber produces dual peak absorption of 99.64% (8.831 GHz) and 99.79% (11.528 GHz) with a Full-Width Half-Maximum (FWHM) bandwidth of 60.88% ranging from 7.616 GHz to 13.704 GHz. Moreover, the microwave absorber is able to have a wide incidence angle of up to 60° for TE and TM modes. Therefore, from the result, it can be concluded that the designed microwave absorber can be applied to the X-band region.